The Role of the Manager of Darud Da'wah Wal-Irsyad Ar-Rahman Galla Raya Islamic Boarding School in Fostering Santri's Morals - Syaifin, Riyo Asmin (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to analyze the role of boarding school managers in developing the morals of students. Islamic boarding schools are Islamic educational institutions that have an important role in shaping the character and morals of the students. This research was conducted with the aim of understanding the contribution of boarding school managers in developing the morals of students. The research method used was a qualitative descriptive method. Data was collected through participant observation, in-depth interviews and documentation studies. The respondents for this research consisted of boarding school managers and a number of students who were interviewed using purposive sampling. The collected data was analyzed thematically to identify the role of boarding school managers in developing the morals of students. The research results show that boarding school managers play a key role in developing the morals of students. They are responsible for creating an educational environment that is conducive and full of moral values. The boarding school management provides continuous guidance and supervision of the students, both in religious and social aspects. They also serve as role models for students in their daily behavior. Apart from that, the boarding school manager has a role as a facilitator in providing comprehensive religious education. They prepare the curriculum and organize activities that support the formation of students' morals. Apart from that, the boarding school management also plays a role in building harmonious relationships between students, both with fellow students and with the surrounding community. This research provides a deeper understanding of the role of boarding school managers in developing the morals of students. It is hoped that the results of this research can be a reference for Islamic boarding school managers in increasing their role in developing the morals of students. Further research can be carried out to expand the scope and involve more variables that influence the moral development of students in Islamic boarding schools.